A special role for the genotype? Some comments on Keith Baverstock: "The gene: An appraisal". (August 2022) - Roll-Hansen, Nils
Abstract: There is at present uneasiness about the conceptual basis of genetics. The gene concept has become blurred and there are problems with the distinction between genotype and phenotype. In the present paper I go back to their role in the creation of modern genetics in the early twentieth century. The terms were introduced by the Danish botanist and geneticist Wilhelm Johannsen in his big textbook of 1909. Historical accounts usually concentrate on this book and his 1911 paper "The Genotype Conception of Heredity." His bean selection experiment of 1900–1903 is generally assumed to be the source of his genotype theory. The present paper examines the scientific context and meaning of this experiment, how it was received, and how the genotype theory became securely established by the early 1910s. I argue in conclusion that the genotype/phenotype distinction, which provides the empirical basis for Johannsen's gene, was scientifically well founded when introduced and still is. Keith Baverstock's criticism does not consider the force of the bean selection experiment at the time and as a paradigm for following investigations of heredity.